Leptin Levels in Various Manifestations of Pulmonary Tuberculosis - Hakan Buyukoglan; Inci Gulmez; Fahrettin Kelestimur; Levent Kart; F. Sema Oymak; Ramazan Demir; Mustafa Ozesmi (Mediators of Inflammation)
Background. Proinflammatory cytokines are prime candidates as causative agents of the metabolic changes that eventually result in tuberculosis-associated weight loss. Microbial products and cytokines such as TNF and IL-1 increase leptin expression dose dependently in adipose tissue. Leptin plays an important role in cellular immunity. Objectives. In this study, we investigated serum leptin and TNF-α levels before and after antituberculosis therapy in patients with active pulmonary tuberculosis (TB). Methods. Twenty five in patients with active pulmonary TB and 18 healthy controls participated in the study. Leptin and TNF-α levels were measured before treatment and six months after the treatment and they were compared with the control group. Body mass index (BMI) and chest X-rays before and after the treatment were also evaluated. Results. The leptin levels before and after the treatment were 1.66±1.68 ng/mL and 3.26±3.81 ng/mL, respectively. The leptin levels of tuberculous patients were significant than in healthy patients (P<.05). The BMI was 19.36±2.55 kg/m2 before the treatment and 22.87±3.13 kg/m2 after the treatment. The TNF-α level was 23.19±12.78 pg/mL before the treatment and 15.95±6.58 pg/mL after the treatment. There was no correlation between leptin and TNF-α levels. Leptin levels were low in patients who had sequela lesion on chest radiographs. Conclusion. Leptin levels are suppressed in tuberculous patients and low leptin levels may contribute to increased susceptibility to infection and recovery with sequela lesions.